PERBEDAAN PENGARUH MUSIK INSTRUMENTAL KITARO DAN MUSIK TRADISIONAL LANGGAM JAWA TERHADAP TINGKAT KECEMASAN ANAK – ANAK SEBELUM TINDAKAN PERAWATAN GIGI - Rizal Saeful Drajat; Erdianto Setya Wardhana; Yayun Siti Rochmah (Odonto : Dental Journal, 2017)
Background: Child anxiety is a worries that comes from unknown sourceand most important factor that caused the problems of child visits to check the condition of oral health to dentist. Music applied as distraction to relieve anxiety, music can provide comfort and relaxation that becomes way to lowering psychological anxiety. Purpose of this study is to determine effect of instrumental music of Kitaro and traditional music of Javanese Langgam on the level of child’s anxiety before dental treatment.Method: Quasi-Experimental research with pretest-posttest design contol group was conducted on 74 samples were divided into 2 groups: instrumental music of Kitaro and traditional music of Javanese Langgam. Anxiety levels were measured by Wong Baker Face Scale questionnaire and pulse. Hypothesis was tested by Wilcoxon test on Wong Baker Face Scale questionnaire and paired sample t-test on measurement of pulse. To determine child’s anxiety level differences between two music were analyzed by Mann-Whitney test.Result: Wilcoxon test results on both music showed p=0.000 and results of paired sample t-test on both music showed p=0.000 this showed there were significant difference between before and after treatment. On Mann-Whitney test showed p=0.096 at Wong Baker Face Scale questionnaire and p=0.006 at pulse measurement, this showed there were significant difference between two groups.Conclusion: From these results concluded that there were difference effect of instrumental music of Kitaro and traditional music of Javanese Langgam in anxiety levels of children before dental treatment.